Rustic chato murciano pig breed: effect of the weight on carcass and meat quality (2019)
Carcass and meat quality parameters of two different weights of pigs from the rustic breed Chato Murciano (Murcia Region, south-eastern Spain) were studied: light weight (LW, 147.98?±?3.78?kg live weight) and heavy weight (HW, 176.07?±?4.78?kg live weight). No weight-dependent effects were observed on carcass quality (carcass yield, length, back fat thickness) or on moisture, pH, and the L* and a* coordinates. The HW group had a higher fat content and cholesterol values than the LW group. None of the fatty acids analysed in the respective meats showed differences between groups (P?>?.05), except C16:0, C18:2 and C18:3. The HW group had higher values for unsaturated and polyunsaturated fatty acids and the n6/n3 index than LW, and lower values for saturated fat and the Saturated/Polyunsaturated fat ratio and a lower Atherogenesis Index. In conclusion, meat and fat quality are influenced by the final live weight of Chato Murciano pigs.